Hepatic inflammation precedes steatosis and is mediated by visceral fat accumulation. Issue 3 (June 2020) - Casagrande, Breno Picin; de Souza, Daniel Vitor; Ribeiro, Daniel Araki; Medeiros, Alessandra; Pisani, Luciana Pellegrini; Estadella, Debora
Abstract : The negative aspects of unhealthy eating on obesity and hepatic health are well described. The axis between the adipose tissue and the liver participates in most of the damage caused to this tissue regarding obesogenic diets (OD). At the same time that the effects of consuming simple carbohydrates and saturated fatty acids are known, the effects of the cessation of its intake are scarce. Withdrawing from OD is thought to improve health; despite some studies had shown improvement in hepatic conditions in the long-term, short-term studies were not found. Therefore, we aimed to determine how OD intake and withdrawal would influence visceral and hepatic fat accumulation and inflammation. To this end, male 60-days-old Wistar rats received standard chow ( n = 16) or a high-sugar/high-fat diet (HSHF) for 30 days ( n = 32), a cohort of the HSHF-fed animals was then kept 48 h on standard chow ( n = 16). In opposition to the generally reported, the results indicate that hepatic inflammation preceded hepatic steatosis. Additionally, inflammatory markers on the liver positively correlated visceral adipokines and visceral fat accumulation mediated them in a deposit-dependent manner. At the same time, a 48-h withdrawal was capable of reverting most of the risen inflammatory mediators, although MyD88 and TNFα persisted and serum non-HDL cholesterol was higher than control levels.